The improvement of titanium reinforced hydroxyapatite for biomedical applications - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2003)
The addition of different amounts of inclusions to brittle hydroxyapatite (HA) gives the advantage of tailoring and predicting the possible mechanical properties of the biocomposite. Biocomposite materials have been developed in order to combine the properties of bioactive material with the better mechanical properties of a second phase. Titanium, having superior biocompatibility, mechanical properties and corrosion resistance, is suitable as a reinforcement phase for biomedical applications. This study focuses on the effects of sintering temperature and the amount of reinforcement phase on the mechanical properties of HA-Ti composites. The HA material used was derived from freshly-extracted human teeth with calcination at 850degreesC. Titanium powders were mixed by 5 and 10 wt % with HA and have been subjected to sintering at 1200 and 1300degreesC for three hours. Density, microhardness, and compressive strength measurements have been carried out. Microstructures have been investigated by SEM and the phase analysis has been determined by the x-ray diffraction analysis. The best mechanical properties have been obtained by sintering at 1300degreesC for three hours with the addition of 10 wt % Ti to HA.
Keywords: biocomposite; hydroxyapatite; titanium